PERBEDAAN PENGARUH MODEL PEMBELAJARAN JIGSAW DAN PEMBELAJARAN KONVENSIONAL TERHADAP KERJASAMA DAN EMPATI SISWA DALAM PENDIDIKAN JASMANI - Nur Fasih; Agi Ginanjar; Nur Mahfuzah Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the difference in the effects between the Jigsaw learning model and the conventional learning model on students’ cooperation and empathy. The research employed an experimental method with an Intact-Group Comparison design. The population of this study consisted of all students of MI PUI Tenajar Lor 1 in the 2024/2025 academic year. The sample involved 52 sixth-grade students, divided into an experimental group of 26 students and a control group of 26 students, selected using a purposive sampling technique. Data were collected through an attitude scale based on the Likert model to measure students’ levels of cooperation and empathy. The findings revealed that the Jigsaw learning model positively influences students’ cooperation and empathy in physical education learning. Furthermore, the study found a significant difference between the Jigsaw learning model and the conventional learning model in their effects on students’ cooperation and empathy.